2023
DOI: 10.1007/s40279-023-01926-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Evidential Value of Mental Fatigue and Exercise Research

Darías Holgado,
Cristian Mesquida,
Rafael Román-Caballero

Abstract: It has often been reported that mental exertion, presumably leading to mental fatigue, can negatively affect exercise performance; however, recent findings have questioned the strength of the effect. To further complicate this issue, an overlooked problem might be the presence of publication bias in studies using underpowered designs, which is known to inflate false positive report probability and effect size estimates. Altogether, the presence of bias is likely to reduce the evidential value of the published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…In several simulation studies, RoBMA was found to be superior to other bias correction methods [28]. RoBMA has been used notably in the field of psychology [31][32][33]. We used RoBMA to provide a sensitivity analysis of i) the publication bias detection, when the Egger's test was significant and ii) the evaluation of the publication bias effect, by providing a corrected ORRoBMA and comparing it to the ORUncorrected as previously described with the T&F method.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In several simulation studies, RoBMA was found to be superior to other bias correction methods [28]. RoBMA has been used notably in the field of psychology [31][32][33]. We used RoBMA to provide a sensitivity analysis of i) the publication bias detection, when the Egger's test was significant and ii) the evaluation of the publication bias effect, by providing a corrected ORRoBMA and comparing it to the ORUncorrected as previously described with the T&F method.…”
Section: Sensitivity Analysismentioning
confidence: 99%